Does the abundance of girellids and kyphosids correlate with cover of the palatable green algae, Ulva spp.? A test on temperate rocky intertidal reefs - Ferguson, A.; Harvey, Euan; Rees, M.; Knott, N. (Blackwell Publishing, 2015)
This study assessed whether the abundance of girellids and kyphosids was related to cover of the palatable green algae, Ulva australis and Ulva compressa, on rocky intertidal reefs in Jervis Bay, New South Wales, Australia. No relationship was found between Ulva spp. cover and abundance of Girella tricuspidata, Girella elevata and Kyphosus sydneyanus during a period of relatively low Ulva spp. cover (i.e. February 2011 to March 2011), but during a period of significantly higher Ulva spp. cover (i.e. October 2011 to November 2011) there was a strong correlation between Ulva spp. cover and G. tricuspidata abundance. Spatial analysis indicated that the abundance of G. tricuspidata was consistent across time, suggesting G. tricuspidata were not moving between reefs in response to variation in Ulva spp. cover between periods but rather that large schools of G. tricuspidata resided on reefs that had relatively higher Ulva spp. cover at certain times of the year.